Older adults' choices of first‐contact care and related factors in Zhejiang and Qinghai Province, China. Issue 9 (24th July 2019) - Hu, Xiaoqian; Zhang, Hao; Sun, Xueshan; Gu, Yuxuan; Zhen, Xuemei; Gu, Shuyan; Li, Yuanyuan; Huang, Minzhuo; Wei, Jingming; Dong, Hengjin
Abstract : Aim: This study aimed to investigate older adults' choices of first‐contact care when they felt ill in Zhejiang and Qinghai province, and the related potential pathways. Methods: Data were from a cross‐sectional survey in Zhejiang and Qinghai. We firstly compared older adults' choices of first‐contact care in two provinces. Then, we applied structural equation modeling to explore pathways from socioeconomic status, accessibility and health status to older adults' choices of first‐contact care. Results: The proportion of older adults who selected primary healthcare institutions as first‐contact care in Qinghai was higher than that in Zhejiang. Socioeconomic status played an important role in the Zhejiang model through direct and indirect pathways. In the Qinghai model, accessibility to primary healthcare institutions was the leading cause for choosing preferred first‐contact care. Conclusions: A better understanding of complex pathways from factors to older adults' choices of first‐contact care was essential, which might inform priorities for further maximizing the utilization of primary care.Geriatr Gerontol Int 2019; 19: 938–944 .